Anatomo-surgical peculiarities of the tumors in the posterior part of the III ventricle - Shamaev, M.; Verbova, L.; Malysheva, T.; Motah, M. (Ukrainian Neurosurgical Journal)
22 tumors of the different types (pinealomas, pineoblastomas, germinomas and astrocytomas ) were investigated at the Institute. Tumor topography and microsurgical anatomy were studied in 22 autopsy cases.The authors determined the causes which limid the radical tumor treatment and also the causes of vital complications.